Optimising primary molecular profiling in non-small cell lung cancer. - R D Schouten; I Schouten; M M F Schuurbiers; V van der Noort; R A M Damhuis; E H F M van der Heijden; J A Burgers; N P Barlo; A S R van Lindert; K W Maas; J J G van den Brand; A A J Smit; et al. (PLoS ONE)
Introduction Molecular profiling of NSCLC is essential for optimising treatment decisions, but often incomplete. We assessed the efficacy of protocolised molecular profiling in the current standard-of-care (SoC) in a prospective observational study in the Netherlands and measured the effect of providing standardised diagnostic procedures. We also explored the potential of plasma-based molecular profiling in the primary diagnostic setting. Methods This multi-centre prospective study was designed to explore the performance of current clinical practice during the run-in phase using local SoC tissue profiling procedures. The subsequent phase was designed to investigate the extent to which comprehensive molecular profiling (CMP) can be maximized by protocolising tumour profiling. Successful molecular profiling was defined as completion of at least EGFR and ALK testing. Additionally, PD-L1 tumour proportions scores were explored. Lastly, the additional value of centralised plasma-based testing for EGFR and KRAS mutations using droplet digital PCR was evaluated. Results Total accrual was 878 patients, 22.0% had squamous cell carcinoma and 78.0% had non-squamous NSCLC. Stage I-III was seen in 54.0%, stage IV in 46.0%. Profiling of EGFR and ALK was performed in 69.9% of 136 patients included in the run-in phase, significantly more than real-world data estimates of 55% (p<0.001). Protocolised molecular profiling increased the rate to 77.0% (p = 0.049). EGFR and ALK profiling rates increased from 77.9% to 82.1% in non-squamous NSCLC and from 43.8% to 57.5% in squamous NSCLC. Plasma-based testing was feasible in 98.4% and identified oncogenic driver mutations in 7.1% of patients for whom tissue profiling was unfeasible. Conclusion This study shows a high success rate of tissue-based molecular profiling that was significantly improved by a protocolised approach. Tissue-based profiling remains unfeasible for a substantial proportion of patients. Combined analysis of tumour tissue and circulating tumour DNA is a promising approach to allow adequate molecular profiling of more patients.